A sacred plant of neuronal effect: the use of ibogaine in addiction treatments in Brazil. (8th July 2022) - Gomes, Bruno Ramos; Tofoli, Luis Fernando
ABSTRACT: This research qualitatively investigated four treatments for addiction in Brazil that use ibogaine as the main tool in the process. Ibogaine is a substance derived from an African plant, Tabernanthe iboga, traditionally used in its region of origin and which leads to intense sensations during its acute effects and also different experiences of oneself and the surrounding world in the period after its use. It's considered a non‐typical psychedelic. We visited the clinics and interviewed professionals and patients of these places. In this article, we focus on how ibogaine is used for addiction and depression treatment and how its effect is understood. There is variation in patient screening and preparation, how the ibogaine is determined, and the care practices proposed after the treatment. These variations seem to be influenced by the context where ibogaine is inserted and their practices. We identified three different contexts that influence ibogaine use in Brazil: the market of addiction treatment clinics, the Brazilian urban religious use of ayahuasca, and the medical context of ibogaine use developed by Howard Lotsof.